2004
DOI: 10.1289/txg.7034
|View full text |Cite
|
Sign up to set email alerts
|

Valproic Acid Teratogenicity: A Toxicogenomics Approach

Abstract: Embryonic development is a highly coordinated set of processes that depend on hierarchies of signaling and gene regulatory networks, and the disruption of such networks may underlie many cases of chemically induced birth defects. The antiepileptic drug valproic acid (VPA) is a potent inducer of neural tube defects (NTDs) in human and mouse embryos. As with many other developmental toxicants however, the mechanism of VPA teratogenicity is unknown. Using microarray analysis, we compared the global gene expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 100 publications
1
31
0
Order By: Relevance
“…Our experiments were done on normal, nonmalignant, uterine tissues which were then exposed to estrogen followed by hyperplasia formation. One more interesting remark, valproic acid, which is used for treatment of epilepsy and has a mechanism of action which involves the blockade of histone deacetylases, revealed expressed teratogenic effects in humans (Phiel et al 2001, Kultima et al 2004. Trichostatin A also has teratogenic effects in vertebrate embryos (Phiel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments were done on normal, nonmalignant, uterine tissues which were then exposed to estrogen followed by hyperplasia formation. One more interesting remark, valproic acid, which is used for treatment of epilepsy and has a mechanism of action which involves the blockade of histone deacetylases, revealed expressed teratogenic effects in humans (Phiel et al 2001, Kultima et al 2004. Trichostatin A also has teratogenic effects in vertebrate embryos (Phiel et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Research both in vivo and in vitro demonstrates that VPA can cause a similar pattern of embryonic malformations such as neural tube defects (NTDs) and craniofacial abnormalities (Bruckner et al 1983;Ceylan et al 2001). However, the mechanism of VPA-induced teratogenesis remains poorly understood, although several biochemical/ molecular modes of action have been put forward to account for VPA action, such as interference with folatemethionine metabolic pathways (Dawson et al 2006;Hishida and Nau 1998;Nosel and Klein 1992;Wegner and Nau 1991), activity as a histone deacetylase inhibitor (Menegola et al 2005;Eikel et al 2006a, b), alteration of gene expression (Finnell 1991;Kultima et al 2004;Okada et al 2005), and generation of reactive intermediates via lipoxygenases or the prostaglandin synthetase co-oxidation pathway (Miranda et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also revealed decreased GSH in liver homogenates and in the mitochondrial content of total glutathione in rats administered a single intraperitoneal dose of VPA (Cotariu et al 1990;Seçkin et al 1999). Genes that code for proteins with antioxidant properties such as metallothioneins and Ltb4dh are induced by VPA in both embryos and murine embryonal carcinoma P19 cells (Kultima et al 2004). Researchers have also found increased oxidative stress in epileptic children treated with VPA (Michoulas et al 2006;Verrotti et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Although the accurate nature of this inhibition has not been described, structural similarity among Hox gene products allows to postulate that adriamycin could have an affinity for more distally-expressed Hox proteins [33]. As a side result of extensive use of ''blind'' microarray technology, alterations in expression of Hox genes have been detected in several embryopathies, as the ones caused by boric acid, cadmium or valproate [34][35][36].…”
Section: Discussionmentioning
confidence: 99%